Exploration of Research and Practice Paths in County-level Senior High Schools: An Empirical Study Based on the "Dual-cycle" Model of Ning'an No.1 Senior High School - Benjun Wang; Bensen Liang; Xiaowei Sui (Education Research on Study Tours and Practice, 2026)
This study takes Ning'an No.1 Senior High School as the primary implementation site.It addresses the structural challenges commonly faced by county-level high school research and study practice,including fragmented resources, disjointed curricula, superficial content, and inadequate collaboration by innovatively proposing an "internal cycle + external cycle" dual-path development model. The internal cycle focuses on deeply developing local natural, historical, cultural, and red educational resources to establish a localized curriculum system. The external cycle expands external study tour exchange channels through partnerships with prestigious institutions such as Tsinghua University and high-quality social practice bases. After three years of action research, a complete four-dimensional system integrating "curriculum + platform + activities + mechanisms" has been established, resulting in a 23.5% increase in the excellence rate of students' comprehensive quality evaluation and providing a replicable solution for the research and study practice of county-level senior high schools.